Assessment of Islamic Bank Soundness: Analysis Using CAMELS, RGEC and ALTMAN Z Score Methods - Shabri, Husni; Hosen, Muhamad Nadratuzzaman (IAIN Kudus, 2023)
The purpose of this study is to analyze the soundness level of PT BCA Syariah. This study is descriptive research with a quantitative approach.The paper used data on the annual financial statements of PT BCA Syariah for the period 2017 - 2021. The analysis using CAMELS, RGEC and Altman Z-Score methods. The results show that overall PT BCA Syariah in the 2017-2021 period was at the Health level in the CAMELS, RGEC and Altman Z-Score assessment methods. The highest health and health condition of PT BCA Syariah during the Covid-19 pandemic is a management effort in carrying out appropriate, focused and planned strategies and risk mitigation. The three analytical methods show the same results so that they can be used as a reference for assessing the health of other Islamic banks